The Florida Agricultural Handbook of Solid and Hazardous Waste Regulation: Resource Conservation and Recovery Act (RCRA) - Michael T. Olexa; Christopher Hill (EDIS, 2023)
Circular 1139, a multi-part handbook, helps Floridians recognize which agricultural and household activities may involve solid and hazardous wastes. It also provides an introduction to the agencies and statutes that govern solid and hazardous waste disposal.